Oxidative stress biomarkers and their relationship with testosterone in male auto mechanics in Ibadan, Nigeria (2016)
Occupational exposure to mixed chemicals generates free radicals with inadequate antioxidants resulting in oxidative stress. Recently, hypogonadism in male auto-mechanics was associated with oxidative stress. Studies show that testosterone, a male hormone increases the activities of antioxidant enzymes. This study is aimed at evaluating the oxidative stress biomarkers and their relationship with testosterone in auto mechanics in Ibadan, Nigeria. Eighty-three males participated in this prospective cross sectional study after informed consent. Forty-three were male auto-mechanics, occupationally exposed to mixed chemicals in the mechanic community, Bodija, Ibadan (cases). Their mean (SEM) age and body mass index (BMI) were 42.5 (1.7) years and 23.8 (0.5) Kg/m2 respectively. They were age and BMI matched with 40 unexposed, apparently healthy males from the University College Hospital and environs (controls). Demography, social habits, anthropometry and gonadal status were obtained by standard methods. Serum obtained from blood (10 ml) collected from the participants was used for biochemical analyses. Testosterone levels were determined by enzyme immunoassay method (Immunometrics UK Ltd). Levels of total antioxidant capacity, total plasma peroxide (TPP), malondialdehyde (MDA), hydrogen peroxide (H2O2), glutathione peroxidase (GPX), superoxide dismutase (SOD), glutathione-S-transferase (GST), and reduced glutathione (GSH) were determined using spectrophotometric methods while oxidative stress index (OSI) was calculated. P<0.05 was regarded as significant. TPP, MDA, OSI, H2O2 and GST `levels were significantly higher (P<0.001) in eugonadal cases compared with controls. All these biomarkers levels were similar in hypogonadal compared with eugonadal cases. (P>0.05) Testosterone related negatively with SOD in the controls only but positively with MDA and negatively with GST in cases only (P<0.05). Occupationally exposed auto mechanics appear to have oxidative stress and may benefit improvement in antioxidant status. Testosterone may contribute to and enhance total antioxidant status, which may be important in gonadal function.